Finance Companies and Small Business Borrowers: An Empirical Investigation - George Haynes; Myles Watts (Journal of Entrepreneurial and Small Business Finance, 1996)
Finance companies have been perceived as isolated and insignificant lenders, attracting high risk borrowers and charging these borrowers relatively high prices. Using the 1988 National Survey of Small Business Finance, this study examines the relationship between finance companies and other lenders, describes the characteristics of borrowers attracted to finance companies and assesses whether finance companies charge higher loan prices and impose more stringent collateral requirements on their borrowers than other lenders. This study refutes the popular notion that finance companies are not mainstream lenders by suggesting that finance companies are an important source of financial capital attracting borrowers similar to those attracted by commercial banks and charging these borrowers competitive prices.
Keywords: L25; G32; G21; 650; Finance Companies; Small Business; Lending; Borrowing